Planning the development of professional Competence of educational entities to achieve sustainable development GOALS - Ponomarova, Halyna; Kharkivska, Alla; Petrichenko, Larisa; Repko, Inna; Vasylenko, Olena (My University, 2025)
This article identifies ways to optimally prepare future teachers to use methods of analysis and synthesis of advanced pedagogical practices. It explores the specifics of using analysis and synthesis in teachers' teaching to correct errors and shortcomings, as well as to disseminate progressive, advanced pedagogical practices. It examines methods of analysis and synthesis as ways to identify the didactic value of advanced pedagogical practices and their creative application within the context of a traditional system of organizing pedagogical practice. The key levels of teachers' readiness to apply analysis and synthesis methods in teaching are determined. Methods have been developed to measure future teachers' readiness to use methods of analysis and synthesis of pedagogical activity. Experimental sites have been created based on the areas of application of methods of analysis and synthesis of pedagogical activity. The study showed that the application of the analysis and synthesis method in the professional training of future teachers can be considered from various perspectives. This applies not only to best pedagogical practices but also to a number of other important pedagogical aspects
Keywords: education; students; competence; methodology; educational Entities; освіта; студенти; компетентність; методологія; освітні установи